The associational economy firms, regions, and innovation - Cooke, Philip (Philip N.); Morgan, Kevin 1953- (Oxford University Press, 1998)
This text explores issues of corporate reorganization in the context of heightened global competition. It concludes that the associational economy may be the "third way" between state and market co-ordination of modern economies.